City as a human development ecosystem: Exploring the characteristics of an entrepreneurial region - Abdul Majid, Izaidin; Dora, Mohd Taib; Ismail, Kamariah; Hussin, Huzili (2007)
It is commonly agreed that entrepreneurial activities is crucial in generating economic development, creating new jobs, promote innovative and creative ideas that will eventually contribute to human development and the economic growth of a country. Economic growth, especially at the regional level and specifically in the formation of regional clusters of industrial innovation, is generally thought to have very close connections with entrepreneurship and new firm formation. In order to help spur entrepreneurial activities, supportive environment for business start-up or entrepreneurial regions should be designed and established. Entrepreneurial regions are perceived to display characteristics that are consistent with economic prosperity and growth. Some of these characteristics are high levels of business start-up, often of high quality ventures and an adaptable and flexible indigenous population of firms that are innovative and trade extensively outside the region as well as creating new economic opportunity within it. On the human or entrepreneurs perspective the issue of culture is an interesting area to be explored. The extent to which a culture of entrepreneurship exists and the extent to which individuals experience enterprise and observe entrepreneurial activity in others around them is an indicator of entrepreneurial potential within the region. This paper therefore, explores and highlights some of these issues pertaining to entrepreneurial region and human development in terms of their entrepreneurial culture. This study reveals that the Multimedia Super Corridor Malaysia fulfills the entire underlying criterion (as proposed in the research framework) of an entrepreneurial region.